Oil and gas production technology - Toporov, V. H.; Bratakh, M. I.; Dobrunov, D. Ye. (Харківський національний автомобільно-дорожній університет, 2017)
This manual training is compiled for readers with an interest in the oil and gas production industry. It contains an overview of the main processes, equipment and fundamentals. This material is published to give the reader a quick overview of the entire upstream area, whilst still preserving enough detail to let the engineer have an appreciation of the main characteristics and design issues. The book has a complete description on the detailed design of any part of upstream process, and many particularities have been omitted in order to summarize a vast subject. The course of lectures is intended for the bachelors of specialty 6.050304 “Oil and gas production” in English.
Keywords: training manual; oil; gas; production technology; processes; equipment; production industry; specialty 6.050304 “Oil and gas production”